2021
DOI: 10.3390/metabo11090639
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Insulin Degludec/Insulin Aspart Compared with a Conventional Premixed Insulin or Basal Insulin: A Meta-Analysis

Abstract: Insulin degludec/insulin aspart (IDegAsp) is a novel co-formulation of 70% insulin degludec and 30% insulin aspart. The present meta-analysis was conducted to assess the efficacy and safety of IDegAsp compared with a conventional premixed insulin or basal insulin. We extracted data from citation databases, including PubMed, EMBASE, and the Cochrane Library, since inception to 2021. We calculated the mean differences for hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), self-measured mean glucose, and postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…19 The reduction in FPG with IDegAsp could be attributed to the long-acting effect of the IDeg analog while HbA1c reduction may be due to the prandial coverage of the IAsp analog. 17 The doses of total daily, prandial and basal insulin were reduced from baseline to EOS in this study; however, these reductions were not statistically significant. A similar trend was observed in a retrospective real-world study in Japan where there was a significant reduction (p<0.0001) in daily basal insulin dose over 26 weeks in patients with T2DM who were administered with IDegAsp.…”
Section: Insulin Dosecontrasting
confidence: 59%
See 3 more Smart Citations
“…19 The reduction in FPG with IDegAsp could be attributed to the long-acting effect of the IDeg analog while HbA1c reduction may be due to the prandial coverage of the IAsp analog. 17 The doses of total daily, prandial and basal insulin were reduced from baseline to EOS in this study; however, these reductions were not statistically significant. A similar trend was observed in a retrospective real-world study in Japan where there was a significant reduction (p<0.0001) in daily basal insulin dose over 26 weeks in patients with T2DM who were administered with IDegAsp.…”
Section: Insulin Dosecontrasting
confidence: 59%
“…20 Also, nine studies in the meta-analysis reported a reduction or no difference in total dose requirement for IDegAsp compared to other basal insulins. 17 In our study, the incidence of overall and nocturnal nonsevere and severe hypoglycemic events was reduced from baseline to EOS. Although the low number of hypoglycemic events did not allow for statistical comparisons, these results suggest that improvement in glycemic control can be achieved with IDegAsp potentially without increased risk of hypoglycemia.…”
Section: Insulin Dosementioning
confidence: 42%
See 2 more Smart Citations
“…22 A MA published in 2021 showed that once-daily IDegAsp is associated with comparable glycaemic control, but a lower risk of nocturnal hypoglycaemia compared with once-daily basal insulins. 23 Both Gla-300 and IDegAsp are approved in several countries, but there is no head-to-head trial comparing them. Therefore, we conducted an SLR and ITC to compare the efficacy and safety of Gla-300 to IDegAsp in patients with T2D inadequately controlled on OADs.…”
Section: Discussionmentioning
confidence: 99%